Exergy Analysis of Energy Systems in Buildings - Gianpiero Evola; Vincenzo Costanzo; Luigi Marletta (Buildings, 2018)
The performance of space heating and cooling systems in buildings is usually measured by applying the first law of thermodynamics, which makes it possible to quantify the energy losses of the single components and to measure their energy conversion efficiency. However, this common approach does not properly consider that different forms of energy have different potentials to produce useful work, the latter being a function of the temperature at which energy is made available. As a result, it is not possible to properly address how the “quality„ of energy is exploited or conserved in the different processes. On the contrary, the second law of thermodynamics is able to do that by introducing the concept of exergy: This is the maximum amount of work that can be produced through an ideal reversible process evolving until a full condition of equilibrium with the environment is attained. Exergy is; thus, a possible way to measure the “quality„ of an energy flow or an energy source. This perspective is particularly relevant when dealing with buildings and their energy conversion systems, which usually deliver thermal energy at a temperature level that is close to the environmental temperature. This means that the users require “low-quality„ energy; notwithstanding, this energy comes from the depletion of “high-quality„ energy sources, such as fossil fuels and electricity. The exergy analysis helps with identifying such irrational use of the energy sources, which cannot come to light from the energy analysis. In this paper, a literature review identifies methods and metrics commonly used to carry out the exergy analysis of buildings and their energy technologies, while also underlining discrepancies and open methodological issues. Then, the review discusses the main lessons learned from selected works, providing significant advice about the rational use of energy in buildings as well as the most effective technological solutions.